Opowiedz mi "Miasto narysowane". O translinearnej możliwości poznawania Lublina z bliska - Jankowski, Jakub (Załącznik Kulturoznawczy, 2023)
Recount The Drawn City to Me: Towards a Translinear Exploration of Lublin The aim of the exercise proposed in this article is to closely read five comic books about Lublin, looking for translinear connections between them. Thus discovered, the links should bring about a peculiar reading experience and reveal a multifaceted perception of Lublin. This “Drawn City” is a mix of folk tales, urban legends, historical facts, and everyday human existence. The proposed translinear reading brings all of these together, offering an insight into the true nature of the city and its residents.